Pendidikan Kewirausahan Kampus Hijau UIN Raden Intan Lampung dalam Mendukung Ekosistem Kota Pintar Bandar Lampung - Iqbal Iqbal (Journal on Education, 2024)
Entrepreneurship is about changing the world through solving social problems, creating innovative products and generating new solutions in life. This research examines how entrepreneurship education at universities or green campuses plays a role in supporting the Bandar Lampung smart city ecosystem. This research is library research with a descriptive approach. The results of this research show that Entrepreneurship Education on an environmentally friendly green campus is an effective way to produce intelligent people as an indicator of creating a smart city based on a green city and a liveable city. Therefore, leaders of green universities or campuses must continue to strive to create environmentally friendly entrepreneurship education so that green campus efforts as part of the green city ecosystem towards a livable city can continue to be implemented towards achieving smart city targets.